Basophil-derived IL-4 promotes epicutaneous antigen sensitization concomitant with the development of food allergy - Hussain, Maryam; Borcard, Loïc; Walsh, Kevin P.; Pena Rodriguez, Maria; Mueller, Christoph; Kim, Brian S.; Kubo, Masato; Artis, David; Noti, Mario (Journal of allergy and clinical immunology, 2018)
Exaggerated thymic stromal lymphopoietin (TSLP) production and infiltration of basophils are associated with the pathogenesis of atopic dermatitis (AD), a recognized risk factor for the development of food allergies. Although TSLP and basophils have been implicated in promotion of food-induced allergic disorders in response to epicutaneous sensitization, the mechanisms by which TSLP-elicited basophils guide the progression of allergic inflammation in the skin to distant mucosal sites, such as the gastrointestinal tract, are poorly understood. We sought to test the role of basophil-intrinsic IL-4 production in TH2 sensitization to food antigens in the skin and effector food-induced allergic responses in the gut. Mice were epicutaneously sensitized with ovalbumin on an AD-like skin lesion, followed by intragastric antigen challenge to induce IgE-mediated food allergy. The requirement for basophil-derived IL-4 production for TH2 polarization and the pathogenesis of IgE-mediated food allergy was assessed in vitro by using coculture experiments with naive T cells and in vivo by using Il4 3′UTR mice that selectively lack IL-4 production in basophils. Epicutaneous food antigen sensitization is associated with infiltration of IL-4–competent innate immune cells to the skin, with basophils and eosinophils representing the predominant populations. In contrast to basophils, absence of eosinophils did not alter disease outcome. Coculture of IL-4–competent basophils together with dendritic cells and naive T cells was sufficient to promote TH2 polarization in an IL-4–dependent manner in vitro, whereas absence of basophil-intrinsic IL-4 production in vivo was associated with reduced food-induced allergic responses. TSLP-elicited basophils promote epicutaneous sensitization to food antigens and subsequent IgE-mediated food allergy through IL-4. Strategies to target the TSLP–basophil–IL-4 axis in patients with AD might lead to innovative therapies that can prevent the progression of allergies to distant mucosal sites. [Display omitted]